EDUCATIONAL PROJECT AS A MEANS OF FORMING OF FUTURE SPECIALISTS' PROFESSIONAL COMPETENCE: A PSYCHOLOGICAL ASPECT - Tetiana Savrasova-V'un (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article highlights the actual problem of the dependence of the psychological component of the professional competence of future specialists on the use of an educational project in the educational process. The purpose of the article is to study the features of the influence of the use of an educational project in the educational activities of a higher educational institution on the psychological component of the professional competence of future specialists. The content and structure of the psychological component of the professional competence of future specialists have been determined, which is considered as a complex of characteristics of future specialists, contains psychological knowledge, skills, motivational, emotional processes, personal properties that help to carry out professional activities, self-improvement, and consists of motivational, emotional, activity, personal, cognitive components. The experience of the formation of the psychological component of the professional competence of future specialists with the help of an educational project introduced into the educational process of the Institute of Philology of Borys Grinchenko Kyiv University is characterized. Among the research tools were used: diagnostic methods for studying the components, indicators of the psychological component of the professional competence of future specialists, the experimental method, the comparison method, and correlation analysis. The relevance of the topic is confirmed by the results of a survey of future specialists who underwent diagnostics on the problems of studying the level of the psychological component of professional competence for use in the educational process of an educational project and after. The experiment involved 227 future specialists in the specialty «035 Philology». Through experimental activities, the features of the application of the educational project in the educational process of the institution have been determined. It was revealed that the level of the psychological component of professional competence before the implementation of the educational project was lower than the level of the studied phenomenon after the application of the project in the educational process. The results of the analysis showed that the process of creating and implementing an educational project by future specialists affects the formation of the psychological component of students' professional competence.